STRATEGI MENINGKATKAN PERAN LEMBAGA KEUANGAN MIKRO PEREMPUAN BERBASI KOMODITI LOKAL DI TOISAPU AMBON - Restia Christianty; Dinatonia Matruty (Cakrawala Management Business Journal, 2019)
in Toisapu Sub Vilage, micro business is dominated by women engaged in the informal sector who are members of a women's business group that has a local commodity processing business (Nutmeg Juice). The development and empowerment of Women's Microfinance Institutions (LKMP) is the right step in supporting the rural economy, because it is able to provide flexible services, especially in financing businesses that are not feasible to be funded by non-bankable financial institutions. This study aims to analyze the role of Hunilai LKMP and analyze internal and external factors to create a strategy to maintain the existence of microfinance institutions. Using the SWOT analysis method. The results of the study showed that the role of the Hunilai LKMP was able to change the wheels of the economy on a micro scale, provide easy access to capital in the form of funds, tools, training and be able to foster the confidence of LKMP Hunilai members in increasing their role in families and communities. The development strategy needed is to create a legal umbrella for LKMPs and other supporting policies in optimizing the role of LKMPs to alleviate poverty in rural areas, increase human resource capacity and strengthen cooperation with other stakeholders.